A Gender perspective on the use of Artificial Intelligence in the African FinTech Ecosystem: Case studies from South Africa, Kenya, Nigeria, and Ghana - Shamira Ahmed (International Telecommunications Society (ITS), 2021)
The use of artificial intelligence (AI) based systems complements the time-sensitive and data intensive nature of many activities in the financial services industry (FSI)-Specifically, in FinTech Ecosystems (FEs) that have disrupted many financial services landscapes in sub-Saharan Africa (SSA). However, FEs have distinct interrelated supply-side and demand-side dynamics that perpetuate gender disparity. As evidenced in many wealthier economies with more AI maturity, technology is not neutral, AI in particular is inherently biased and magnifies pervasive gender and racial discrimination that exist in the ecosystems where it is deployed. This raises questions regarding the manner in which AI can exacerbate or alleviate current dynamics in inequitable and unfair ecosystems. With the aforementioned in mind, this paper adopts a gender lens to examine the potential impact of using AI based systems in the FEs of four SSA countries-South Africa, Kenya, Nigeria, and Ghana.
Keywords: 330